Asset divestments, economic crisis, and the future performance of companies - Moraes, Simone Dias de; Nossa, Silvania Neris; Moreira, Nádia Cardoso; Brugni , Talles Vianna (Contextus - Revista Contemporânea de Economia e Gestão, 2022)
This paper investigated the impact of asset divestments made by financially constrained companies on their future performance, as well as their potential for reversing past losses. After applying the pairing of the companies listed, the estimation of the relationships of the variables took place through GMM and LOGIT. The research findings indicate that there is evidence that the sale of assets by companies with financial constraints contributes to future performance. A contribution of this research is for managers who have empirical results that have not yet been discussed in the Brazilian literature and that can serve as support in decision-making on the policy of selling or maintaining assets.